Preparation and Optical Characterization of Poly (Vinyl Alcohol): Eosin-Y Films Synthesized by Solvent Casting Method: التحضير والتوصيف البصري للبولي (كحول الفينيل): أفلام Eosin-Y المُصنّعة بطريقة الصب بالمذيبات - A.H, Nour; Israa M. abdulraheem (ASJ - Academic Science Journal, 2024)
The effect of Eosin-Y doped in PVA on the optical properties of the composite films was found to be intentional as PVA films were deposited by solvent casting process with a thickness of 25 ± 1 μm and were grafted with different absorptions of Eosin-Y. The optical diffusion (%) in the wavelength range 200–900 nm as well as the effect of doping ratio on the optical parameters of the prepared films were described. The results showed that the layers showed acceptable indirect developments in the interbands, which are affected by the doping ratios. The band gap of the doped films decreased to 2.20 eV, 2.17 eV, and 2.13 eV for doping ratios of 2%, 4%, and 6%, respectively, compared to the pure film’s 3.89 eV.